Association of downregulation of WWOX with poor prognosis in patients with intrahepatic cholangiocarcinoma after curative resection. Issue 2 (February 2015) - Huang, Changjun; Tian, Yuan; Peng, Rui; Zhang, Changhe; Wang, Dong; Han, Sheng; Jiao, Chenyu; Wang, Xing; Zhang, Hai; Wang, Yun; Li, Xiangcheng
Abstract Background and Aim Downregulation of the WW domain containing oxidoreductase (WWOX) has been reported to be involved in tumorigenesis in several neoplasms. This study sought to investigate the expression and role of WWOX in intrahepatic cholangiocarcinoma (ICC). Methods WWOX expression was measured by quantitative real‐time polymerase chain reaction (PCR), immunoblot, immunofluorescence, and immunohistochemistry. The prognostic significance was assessed by Kaplan–Meier and Cox regression analyses. The role of WWOX in proliferation, anchorage‐independent growth, gene expression regulation, and tumorigenesis was assessed by WWOX re‐expression using lentivirus. Methylation‐specific PCR was performed to evaluate the methylation status of the WWOX gene regulatory region. A DNA methyltransferase inhibitor, 5‐aza‐2′‐deoxycytidine (AZA), was used to activate the endogenous WWOX gene in ICC cells both in vitro and in vivo. Results The expression of WWOX in ICC tissues was much lower than that in nontumorous samples and showed reverse correlation with proliferative status. Restoration of WWOX expression resulted in suppression of the growth of WWOX‐deficient ICC cells through activation of the intrinsic apoptotic signaling pathway, but did not affect growth of WWOX‐sufficient human intrahepatic biliary epithelial derived non‐cancer cells. Multivariate analyses revealed that downregulation of WWOX was an unfavorable predictor for overall survival and cumulative recurrence rates. The WWOX gene regulatory region was frequently methylated in ICC tissues and cell lines, and intratumoral WWOX restoration, through AZA injection, suppressed tumor growth in nude mice. Conclusion Downregulation of WWOX may occur as a result of hypermethylation and implies a poor prognosis in ICC; WWOX re‐expression may be a potential molecular therapeutic target for ICC.